Physicochemical and functional properties of extruded wheat bran dietary fiber: Effects on slow transit constipation - Wang, Zhan; Tan, Dong; Zhao, Kemeng; Shen, Wangyang; Jia, Xiwu; Liu, Bo (Italian Journal of Food Science, 2025)
This study investigated wheat bran dietary fiber (WBDF) using the twin-screw extrusion method, with wheat bran as the primary raw material. The research examined the physicochemical properties, cholesterol and sodium cholate adsorption capacity, thermogravimetric analysis, X-ray diffraction, and functional characteristics. Animal experiments were conducted to assess its impact on improving constipation. Results indicated that extru-sion-modified WBDF (E-WBDF) exhibited higher water-holding capacity (WHC), oil-holding capacity (OHC), water swelling capacity (WSC), and stronger cholesterol and sodium cholate adsorption capacities (CAC and SCAC). Additionally, E-WBDF showed greater DPPH and ABTS scavenging activities compared to WBDF. In mouse models of slow transit constipation, both WBDF and E-WBDF significantly alleviated constipation, with E-WBDF demonstrating superior efficacy. These findings highlight that E-WBDF could serve as a promising functional food additive to enhance intestinal function.